A Study on Teaching Reading Comprehension at SMK Wijaya Kusuma Surakarta - Ihwan Aji Suryana (English Education Department Slamet Riyadi University Surakarta, 2021)
Pandemic covid-19 or corona virus disease forced many schools in Indonesia to apply online learning. The purpose of the study was to describe the problems in teaching reading comprehension before and during pandemic covid-19. The method of this research was descriptive qualitative research. The subject of the research was the English teacher of eleventh grades and the students of XI-C in SMK Wijaya Kusuma Surakarta. The data were collected through questionnaires and interview. The questionnaires were given to English teacher and the students of XI-C SMK Wijaya Kusuma Surakarta. The data were analyzed used qualitative data analysis. The data were analyzed through the process of 1) data reduction, 2) data display, 3) data collection, 4) conclusion drawing/verification. Interestingly, the study found that the problems of teaching reading comprehension before pandemic covid-19 were: 1) the students had difficulty to finding main idea and detail information, 2) the students had difficulty to comprehend sentence in teaching reading comprehension, 3) the students get nervous and less motivation when reading English text, 4) the different ability of students. While, during pandemic covid- 19 the problems in teaching reading comprehension were: 1) internet connection and signal, 2) limited internet quota, 3) slow responds, 4) prefer face to face learning. The study recommends that other researcher to development kinds of media online learning to implement effective teaching and learning process. Keywords: Reading Comprehension, Teaching Reading, Online Learning